KOMUNIKASI PARIWISATA DALAM PENGEMBANGAN PASAR KREATIF VAN DER CAPELLEN SEBAGAI DESTINASI WISATA KREATIF KABUPATEN TANAH DATAR - Amita Raharjo; Noor Efni Salam (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Tourism is a trend that is growing quite rapidly and is considered a promising industry, because tourism has many benefits for society in terms of economy, culture, environment, science, and others. Historical potential is one of Tanah Datar's great assets in developing its tourism. The fort vandercapellen fort is a relic of the Dutch era, now this fort has changed its function to become a tourism, youth and sports office and is used as a fort vandercapellen traditional market that sells typical MinangKabau food / drinks. Therefore, the Tanah Datar community must work together and work together to promote the authentic Minangkabau flatland as a branding in the Tanah datar district, so that it continues to increase economic growth and the welfare of the community. This study aims to determine the background of the van der capellen creative market as a creative tourism destination in Tanah Datar district and to find out the GenPi tourism communication strategy in developing the van der capellen creative market as a creative tourist destination. This study used a qualitative research method, the research subjects were 3 people who were selected using purposive technique, the main informants in this study were 2 people from the tourism, youth and sports offices, the GenPi (GenerasiPesona Indonesia) and the manager of promotion and tourism information at tourism promotion section as well as from the community as supporters. Data collection was carried out through interviews, observation and documentation. Data analysis techniques are data reduction, data collection, data presentation, drawing conclusions and evaluation using data validity checking techniques, namely participation extension and triangulation. The results of this study indicate that to determine the background of the van der capellen market as a creative tourist destination for flatland regencies, to determine the tourism communication strategy in developing the van der capellen creative market is to promote the van der capellen creative market in various media, both print and media. no, building a shop / stall that will be used by merchants to sell is done to improve the standard of living of the surrounding community, create photo spots with the MinangKabau concept in the past, to transact visitors using a special coin of one coin worth Rp. 2,500